A Fe-NC nanomaterial prepared based on a dual-mode method, preparation method and application in fuel cells

Fe-N-C nanomaterials were synthesized by the dual-template method, and the use of silica and mesoporous g-C3N4 templates solved the problem of limited active sites of Fe-N-C nanomaterials in the prior art, and achieved atomically dispersed Fe single atom load, significantly improving the performance of oxygen reduction reaction.

CN116281952BActive Publication Date: 2025-03-21CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310115580.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-15
Publication Date
2025-03-21
Estimated Expiration
2043-02-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively synthesize atomically dispersed Fe-N-C nanomaterials, resulting in limited exposure of active sites for oxygen reduction reactions and poor migration performance.

Method used

The Fe-N-C nanomaterials were synthesized by the double-template method, and silica and mesoporous g-C3N4 were used as templates, and prepared by chemical reduction methods, synergistically providing sufficient active sites and dispersing Fe single atoms.

Benefits of technology

The active site and oxygen reduction reaction of Fe-N-C nanomaterials are improved, and the catalytic performance of oxygen reduction exceeds the performance of commercial Pt/C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116281952B_ABST
    Figure CN116281952B_ABST
Patent Text Reader

Abstract

The present invention discloses a Fe-N-C nanomaterial prepared based on a dual-mode method, a preparation method and an application in a fuel cell. The preparation method of the present invention comprises the following steps: (1) evaporating a solution consisting of dicyandiamide, a carbon source, an iron source, mesoporous g-C3N4, nano-silicon dioxide and water to obtain an evaporated product; (2) calcining the evaporated product under an inert atmosphere to obtain a calcined product; (3) etching the calcined product after cooling to remove silicon dioxide, and freeze-drying after etching to obtain the Fe-N-C nanomaterial (SA-Fe / NC-NPC). The present invention uses nano-silicon dioxide spheres and mesoporous g-C3N4 as templates, and the g-C3N4 template provides an effective metal-N bond for the stable existence of a single atom, and the silicon dioxide template provides a good spatial confinement effect, and a synergistic effect is generated between the two templates, which not only provides sufficient active sites, but also increases the specific surface area, and synthesizes a porous carbon catalyst material doped with nitrogen loaded by atomically dispersed Fe sites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of cathode catalysts for fuel cells, and specifically relates to a Fe-NC nano material prepared based on a dual-mode method, a preparation method and application in fuel cells. Background Art

[0002] Fuel cells play an important role in the energy field. Oxygen reduction reaction, as an important reaction of this energy conversion device, is the bottleneck of effective electrochemical energy conversion. Precious metal platinum-based materials are the most active oxygen reduction (ORR) catalysts known so far, but their yield is low and their price is expensive. Therefore, the rational development and design of non-platinum catalysts with outstanding performance as electrode materials is the key to improving advanced energy conversion and solving energy problems. Nanomaterials based on transition metal-nitrogen-carbon (MNC, M=Fe, Co, etc.) can effectively regulate the local electronic structure of oxygen reduction, optimize the adsorption free energy of intermediates, and improve catalytic activity, becoming an ideal substitute for platinum-based catalysts. Single atom catalysts (SACs) are catalysts composed of only atomically isolated active centers with a particle size of less than 1nm. SACs expose all metal atoms on the surface, which can not only achieve 100% atomic utilization efficiency, but also have uniformly distributed active sites, which is particularly attractive for reducing the cost of metal catalytic materials and improving catalytic activity. However, single atom materials are easy to agglomerate due to their small size. Therefore, using carbon materials as substrates can not only support and disperse metals, but also achieve high-density MNC sites during annealing due to their high surface area. The traditional preparation method is to directly pyrolyze the mixture of nitrogen, carbon and transition metal precursors, which often makes it difficult to control the porous structure, resulting in the aggregation of metal atoms to form particles, which leads to limited exposure of ORR active sites and poor migration performance. Therefore, it is still a challenge to design and synthesize atomic-level dispersion of MNC sites and regulate the electronic coordination of active sites. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a Fe-NC nanomaterial prepared based on a dual-mode method, a preparation method and an application in a fuel cell. The Fe-NC nanomaterial is synthesized by chemical reduction and a dual-template synthesis method, combined with silica and mesoporous g-C3N4 porous structure characteristics, wherein g-C3N4 can be used as a soft template to guide the catalyst to form a sheet-like porous structure, and can also be used as a metal ligand to anchor metal ions; secondly, silica has high stability and good spatial confinement, and can strictly control the size and morphology of carbon materials. The two templates produce a synergistic effect, which not only provides sufficient active sites, but also can fully disperse Fe single atoms due to its high specific surface area. The Fe-NC nanomaterial synthesized under dual-template conditions contains more mesopores than the conventional single-template synthesized material, and as the proportion of silica increases, the mesoporosity contained in the sample increases, which effectively improves the active sites of the Fe-NC nanomaterial and the stability and service life in the oxygen reduction reaction. The method of the invention is simple to operate. The Fe-NC nanomaterial is a nitrogen-doped porous carbon catalyst material (SA-Fe / NC-NPC) supported by an atomically dispersed Fe single-atom site catalyst, which can be used as a non-platinum catalyst for oxygen reduction reactions and fuel cell cathodes.

[0004] In a first aspect, the present invention provides a method for preparing a Fe-NC nanomaterial, comprising the following steps:

[0005] (1) evaporating a solution consisting of dicyandiamide, a carbon source, an iron source, mesoporous g-C3N4, nano-silica and water to obtain an evaporation product;

[0006] (2) calcining the evaporated product under an inert atmosphere to obtain a calcined product;

[0007] (3) After cooling the calcined product, etching is performed to remove silicon dioxide, and after etching is completed, freeze-drying is performed to obtain the Fe-NC nanomaterial.

[0008] In the present invention, the g-C3N4 template provides an effective metal-N bond for the stable existence of single atoms, and the silica template provides a good spatial confinement effect to control the morphology and size of the material. In addition, the two templates produce a synergistic effect, which not only provides sufficient active sites for the carbon material, but also its high specific surface area can fully disperse the Fe single atom, thereby obtaining excellent oxygen reduction performance.

[0009] In the above preparation method, the carbon source is zinc gluconate;

[0010] The iron source is a divalent iron salt or a trivalent iron salt;

[0011] The divalent iron salt is preferably ferrous sulfate, ferrous nitrate or ferrous chloride;

[0012] The tertiary iron salt is preferably ferric acetylacetonate, ferric chloride, ferric nitrate or ferric acetate;

[0013] Wherein, the divalent iron salt and the trivalent iron salt can be added in the form of their hydrates according to the characteristics of the salts;

[0014] The particle size of the nano silicon dioxide is 20 to 50 nm, such as 30 nm;

[0015] The mass ratio of the dicyandiamide, the carbon source, the iron source, the mesoporous g-C3N4, the nano-silicon dioxide and the water is (3-5): 1: (0.5-1): (3-5): (5-7): (400-600), such as 4: 1: 0.5: 3.5: 6: 500. If the ratio of the metal salt to the two templates is too low, the metal loading will be small; if the ratio of the metal salt to the two templates is too high, the metal loading will increase and the metal nanoparticles will aggregate, which is not conducive to improving the electrochemical performance.

[0016] In the above preparation method, the solution composed of dicyandiamide, carbon source, iron source, mesoporous g-C3N4, nano-silica and water is prepared by the following steps: adding the dicyandiamide to water to obtain a dicyandiamide solution; adding the carbon source, the iron source, the mesoporous g-C3N4 and the nano-silica to the dicyandiamide solution in sequence, wherein after adding the nano-silica, the mixed solution is stirred at 500rpm to 800rpm for 16 to 18h. The stirring speed can be, for example, 700rpm. The appropriate stirring time can make the solution mixed evenly. If it is less than 16h, the mixing will be uneven, and if it exceeds 18h, the energy consumption will increase.

[0017] In the above preparation method, the evaporation temperature is 45° C. to 65° C., such as 55° C. During the rotary evaporation, if the temperature is lower than 45° C., the solvent evaporates slowly, while if the temperature is higher than 65° C., the solvent evaporates too quickly and easily boils violently.

[0018] In the above preparation method, the calcination conditions are as follows: heating to 700-1000°C at a heating rate of 2-5°C / min, and maintaining for 2-4h. For example, heating to 900°C, 800°C, 700°C or 1000°C at a heating rate of 3°C / min, and maintaining for 3h. The inert gas can specifically be argon, which can prevent oxidation of the sample during the calcination process. Calcination temperatures below 700°C are not conducive to the formation of Fe single atoms, while calcination temperatures exceeding 1000°C will cause the template to collapse and reduce the electrochemical performance.

[0019] In the above-mentioned preparation method, the etching adopts a hydrofluoric acid aqueous solution with a mass concentration of 15% to 30%, such as 20%; if the concentration is lower than 15wt%, the etching effect cannot be achieved, and if the concentration is higher than 30wt%, the etching speed will be too fast, affecting the pore structure of the catalyst;

[0020] The etching time is 6 to 18 hours, such as 12 hours.

[0021] In the above-mentioned preparation method, the mesoporous g-C3N4 is prepared according to a method comprising the following steps:

[0022] 1) Mix cyanamide and nano silica gel dispersion, and heat and evaporate to dryness;

[0023] 2) grinding the solid evaporated from step 1) into powder and calcining;

[0024] 3) The powder after calcination and cooling in step 2) is etched to remove silicon dioxide, and then washed and freeze-dried in sequence to obtain the mesoporous g-C3N4.

[0025] Furthermore, the role of cyanamide is to dope N. If the ratio is too low, the amount of N doping is too little, and the optimal electrochemical performance cannot be achieved. If the ratio is too high, the N doping will be uneven, resulting in reduced electrochemical performance. The mass ratio of the cyanamide to the nano-silica gel dispersion is (2-3):1, such as 2.4:1;

[0026] The mass concentration of the nano-silica gel dispersion can be 20% to 40%, such as 30%;

[0027] The particle size of the nano silica gel may be 20-50 nm, such as 30 nm.

[0028] Furthermore, the temperature of heating and drying in step 1) may be 110-140° C., such as 130° C.;

[0029] In step 2), the calcination conditions are as follows: heating to 400-700°C at a heating rate of 2-5°C / min and maintaining for 3-5 hours; for example, heating to 450-550°C, 550°C or 450°C at a heating rate of 3°C / min and maintaining for 4 hours. If the temperature is lower than 400°C, the mesoporous structure cannot be formed, and if it is higher than 700°C, the pore mesoporous structure will collapse, which is not conducive to forming a uniform mesoporous structure.

[0030] The etching in step 3) uses a hydrofluoric acid aqueous solution with a mass concentration of 15% to 30%, such as 20%; if the concentration is lower than 15wt%, the etching effect cannot be achieved, and if the concentration is higher than 30wt%, the etching speed will be too fast, affecting the pore structure of the catalyst;

[0031] The etching time in step 3) is 6 to 18 hours, such as 12 hours;

[0032] The washing in step 3) can be carried out using ethanol and water.

[0033] In a second aspect, the present invention provides a Fe-NC nanomaterial prepared by any of the methods described above.

[0034] In a third aspect, the present invention provides the use of the Fe-NC nanomaterial in any of the following:

[0035] A1) Electrocatalytic oxygen reduction reaction;

[0036] A2) preparing a catalyst for electrocatalytic oxygen reduction reaction;

[0037] A3) electrocatalyzing oxygen reduction reaction in a fuel cell;

[0038] A4) preparing a catalyst for the oxygen reduction reaction at the cathode of a fuel cell.

[0039] The present invention has the following beneficial effects:

[0040] (1) The present invention uses nano-silica spheres and mesoporous g-C3N4 as templates, and the two templates produce a synergistic effect, which not only provides sufficient active sites but also increases the specific surface area. Atomically dispersed Fe sites loaded with nitrogen-doped porous carbon catalyst materials are successfully synthesized through a dual-template method.

[0041] (2) The present invention uses transition metal-based catalysts as ORR electrocatalysts, which are inexpensive and readily available. The prepared Fe single atom-N doped porous carbon catalyst exhibits an oxygen reduction half-wave potential of 0.904 V in 0.1 M KOH, and the electron transfer number is about 3.98 (0.2-0.8 V relative to the standard hydrogen electrode), which is better than commercial Pt / C.

[0042] (3) The atomically dispersed Fe site-loaded nitrogen-doped porous carbon catalyst material synthesized by the present invention has a metal size of less than 1 nm and is evenly dispersed, and a small total doping amount of metal elements, which is conducive to the large-scale application of non-precious metal catalysts in fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 TEM image of the Fe-NC nanomaterial prepared in Example 1;

[0044] Figure 2 HAADF-STEM image of the Fe-NC nanomaterial prepared in Example 1;

[0045] Figure 3 A comparison diagram of the ORR polarization curves of the Fe-NC nanomaterial prepared in Example 1 and commercial Pt / C;

[0046] Figure 4 HAADF-STEM image of the Fe-NC nanomaterial prepared in Example 2;

[0047] Figure 5 TEM image of Fe-NC nanomaterial prepared in Comparative Example 2;

[0048] Figure 6 This is the TEM image of the Fe-NC nanomaterial prepared in Comparative Example 3. DETAILED DESCRIPTION

[0049] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0050] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.

[0051] Example 1

[0052] The Fe-NC nanomaterials were prepared according to the following steps:

[0053] (1) Weigh 24 g of cyanamide and 10 g of nano-silica gel dispersion (silica gel particle size is 30 nm, silica gel concentration in the dispersion is 30 wt%, solvent is water), mix and stir evenly, put into an oil bath and heat at 130 ° C to evaporate. Put the evaporated solid into a mortar and grind it into a uniform fine powder, then transfer it to a porcelain boat. Put it in a muffle furnace, heat to 550 ° C at a heating rate of 3 ° C / min, and maintain for 4 hours. When cooled to room temperature, take out the solid powder, and the sample is light yellow. Etch with 20wt% HF for 12 hours. Finally, wash with ethanol and water 2-3 times respectively, put it in a vacuum freeze dryer to freeze-dry the water to obtain mesoporous C3N4.

[0054] (2) Dissolve 0.4 g of dicyandiamide in 50 mL of deionized water and stir until completely dissolved. Then, add 0.1 g of zinc gluconate to the above solution and stir until completely dissolved. Add 50 mg of ferric acetylacetonate and 0.35 g of the mesoporous g-C3N4 prepared in step (1) to the solution and stir for 1 h. Finally, add 0.6 g of nano-silica beads (30 nm) to the above solution and stir thoroughly at 700 rpm overnight for 18 h. Evaporate the mixed solution to dryness using a rotary evaporator at 55 ° C to obtain a white solid. The dried white solid product was heated to 900 ° C at a heating rate of 3 ° C / min in an Ar atmosphere and maintained at this temperature for 3 h. After the sample was cooled to room temperature, the obtained product was etched with 20wt% HF for 12 h. Then, by freeze drying, the Fe single atom-N doped porous carbon catalyst (SA-Fe / NC-NPC-900) was obtained.

[0055] The TEM image of the Fe-NC nanomaterial prepared in this example is shown in Figure 1 ,from Figure 1 It can be seen that the Fe-NC nanomaterial exhibits a three-dimensional porous material structure, and it can be clearly observed that the size of the pores in the material is in the range of 10-50 nm, indicating that the porous carbon material was successfully prepared.

[0056] The HAADF-STEM image of the Fe-NC nanomaterial prepared in this example is shown in Figure 2 ,from Figure 2 It can be seen that the surface single atoms of Fe-NC nanomaterials are evenly distributed, indicating the generation of Fe single atom-N doped porous carbon materials.

[0057] The ORR catalytic activity of the Fe-NC nanomaterial prepared in this example and commercial Pt / C was tested respectively, and the test conditions were as follows: 5 mg of the catalyst sample was dispersed in 1 mL of a 3:1 mixed solution of isopropanol and water, and 0.5 wt% Nafion solution (10 μL) was added as a binder. Then ultrasonic treatment was performed for 1 hour to form a homogeneous catalyst ink, and 20 μL of the catalyst ink was pipetted onto a rotating disk electrode to dry. In an O2-saturated 0.1 M KOH electrolyte, a standard three-electrode system was used (Ag / AgCl (saturated KCl solution) as the reference electrode, a graphite rod as the counter electrode, and a rotating disk electrode (5 mm in diameter) as the working electrode). The comparison of the ORR polarization curves of the Fe-NC nanomaterial prepared in this example and commercial Pt / C is shown in FIG. Figure 3 ,from Figure 3 It can be seen that the Fe-NC nanomaterial SA-Fe / NC-NPC-900 prepared in this example has a maximum half-wave potential (E 1 / 2 =0.904V) relative to standard hydrogen electrode), Pt / C (E1 / 2 =0.851 V), indicating that the atomically dispersed Fe-NC nanomaterials (SA-Fe / NC-NPC-900) prepared in this system at 900 °C have excellent ORR catalytic activity in alkaline electrolyte.

[0058] Example 2

[0059] The Fe-NC nanomaterials were prepared according to the following steps:

[0060] (1) The experimental steps are the same as step (1) of Example 1.

[0061] (2) Dissolve 0.4 g of dicyandiamide in 50 mL of deionized water and stir until completely dissolved. Then, add 0.1 g of zinc gluconate to the above solution and stir until completely dissolved. Add 50 mg of ferric acetylacetonate and 0.35 g of mesoporous g-C3N4 to the solution and stir for 1 h. Finally, add 0.6 g of nano-silica beads (30 nm) to the above solution and stir thoroughly overnight. At 55 ° C, the mixed solution was evaporated to dryness using a rotary evaporator to obtain a white solid. The dried white solid product was heated to 800 ° C in an Ar atmosphere at a heating rate of 3 ° C / min, and maintained at this temperature for 3 h. After the sample was cooled to room temperature, the obtained product was etched with 20wt% HF for 12 h. Then, by freeze drying, the Fe single atom-N doped porous carbon catalyst (SA-Fe / NC-NPC-800) was obtained.

[0062] from Figure 4 It can be seen that the surface of the Fe-NC nanomaterial prepared in this example contains single atoms, indicating that Fe single atom-N doped porous carbon material is generated.

[0063] Comparative Example 1

[0064] (1) The experimental steps are the same as step (1) of Example 1.

[0065] (2) First, 0.4 g of dicyandiamide was dissolved in 50 mL of deionized water and stirred until completely dissolved. Then, 0.1 g of zinc gluconate was added to the above solution and stirred until completely dissolved. Immediately, 0.35 g of mesoporous g-C3N4 was added to the solution and stirred for 1 h. Finally, 0.6 g of nano-silica beads (30 nm) were added to the above solution and stirred thoroughly at 700 rpm overnight. At 55 ° C, the mixed solution was evaporated to dryness using a rotary evaporator to obtain a white solid. The dried white solid product was heated to 900 ° C in an Ar atmosphere at a heating rate of 3 ° C / min, and maintained at this temperature for 3 h. After the sample was cooled to room temperature, the obtained product was etched with 20wt% HF for 12 h. Then, by freeze drying, a metal-free N-doped porous carbon (NC) material was obtained.

[0066] Example 3

[0067] The Fe-NC nanomaterials were prepared according to the following steps:

[0068] (1) Weigh 24g of cyanamide and 10g of nano-silica gel dispersion (silica gel particle size is 30nm, silica gel concentration in the dispersion is 30wt%, solvent is water), mix and stir evenly, put into an oil bath and heat at 130℃ to evaporate. Put the evaporated solid into a mortar and grind it into a uniform fine powder, then transfer it to a porcelain boat. Put it into a muffle furnace, heat it to 450℃ at a heating rate of 3℃ / min, and maintain it for 4h. When it cools to room temperature, take out the solid powder, and the sample is light yellow. Etch with 20wt% HF for 12h. Finally, wash with ethanol and water 2-3 times respectively, put it into a vacuum freeze dryer to freeze-dry the water, and obtain mesoporous C3N4. .

[0069] (2) Dissolve 0.4 g of dicyandiamide in 50 mL of deionized water and stir until completely dissolved. Then, add 0.1 g of zinc gluconate to the above solution and stir until completely dissolved. Add 50 mg of ferric acetylacetonate and 0.35 g of mesoporous g-C3N4 to the solution and stir for 1 h. Finally, add 0.6 g of nano-silica beads (30 nm) to the above solution and stir thoroughly at 700 rpm overnight. At 55 ° C, the mixed solution was evaporated to dryness using a rotary evaporator to obtain a white solid. The dried white solid product was heated to 900 ° C in an Ar atmosphere at a heating rate of 3 ° C / min, and maintained at this temperature for 3 h. After the sample was cooled to room temperature, the obtained product was etched with 20wt% HF for 12 h. Then, by freeze drying, the Fe single atom-N doped porous carbon catalyst was obtained.

[0070] Example 4

[0071] The Fe-NC nanomaterials were prepared according to the following steps:

[0072] (1) The experimental steps are the same as step (1) of Example 1.

[0073] (2) Dissolve 0.4 g of dicyandiamide in 50 mL of deionized water and stir until completely dissolved. Then, add 0.1 g of zinc gluconate to the above solution and stir until completely dissolved. Add 50 mg of ferric acetylacetonate and 0.35 g of mesoporous g-C3N4 to the solution and stir for 1 h. Finally, add 0.6 g of nano-silica beads (30 nm) to the above solution and stir thoroughly overnight. At 55 ° C, the mixed solution was evaporated to dryness using a rotary evaporator to obtain a white solid. The dried white solid product was heated to 700 ° C in an Ar atmosphere at a heating rate of 3 ° C / min, and maintained at this temperature for 3 h. After the sample was cooled to room temperature, the obtained product was etched with 20wt% hydrofluoric acid solution for 12 h. Then, by freeze drying, the Fe single atom-N doped porous carbon catalyst was obtained.

[0074] Example 5

[0075] (1) The experimental steps are the same as step (1) of Example 1.

[0076] (2) Dissolve 0.4 g of dicyandiamide in 50 mL of deionized water and stir until completely dissolved. Then, add 0.1 g of zinc gluconate to the above solution and stir until completely dissolved. Add 50 mg of ferric acetylacetonate and 0.35 g of mesoporous g-C3N4 to the solution and stir for 1 h. Finally, add 0.6 g of nano-silica beads (30 nm) to the above solution and stir thoroughly overnight. At 55 ° C, the mixed solution was evaporated to dryness using a rotary evaporator to obtain a white solid. The dried white solid product was heated to 1000 ° C in an Ar atmosphere at a heating rate of 3 ° C / min, and maintained at this temperature for 3 h. After the sample was cooled to room temperature, the obtained product was etched with 20wt% hydrofluoric acid solution for 12 h. Then, by freeze drying, the Fe single atom-N doped porous carbon catalyst was obtained.

[0077] Comparative Example 2

[0078] (1) The experimental steps are the same as step (1) of Example 1.

[0079] (2) Dissolve 0.4 g of dicyandiamide in 50 mL of deionized water and stir until completely dissolved. Then, add 0.1 g of zinc gluconate to the above solution and stir until completely dissolved. Add 50 mg of ferric acetylacetonate and 0.35 g of the mesoporous g-C3N4 obtained in step (1) to the solution respectively, and stir thoroughly overnight at 700 rpm for 18 hours. At 55°C, the mixed solution was evaporated to dryness using a rotary evaporator to obtain a white solid. The dried white solid product was heated to 900°C in an Ar atmosphere at a heating rate of 3°C / min, and maintained at this temperature for 3 hours. After the sample was cooled to room temperature, the obtained product was etched with 20wt% HF for 12 hours. Then, by freeze drying, a catalyst without the addition of nano-silica beads was obtained.

[0080] The TEM image of the Fe-NC nanomaterial prepared in this comparative example is shown in Figure 5 ,from Figure 5 It can be seen that the Fe-NC nanomaterial exhibits a three-dimensional porous material structure, but it can be observed that there is an obvious pore aggregation phenomenon, indicating that without adding nano-silica beads, only using nano-silica gel dispersion as a template will cause a certain aggregation of the pores. From the ORR electrochemical test, the half-wave potential of the catalyst prepared in this comparative example is only 0.796V, which is much lower than the half-wave potential of 0.904V of the catalyst with nano-silica beads (Example 1).

[0081] Comparative Example 3

[0082] (1) Weigh 24 g of cyanamide solid and grind it into a uniform fine powder in a mortar, then transfer it to a porcelain boat. Place it in a muffle furnace, heat it to 550°C at a heating rate of 3°C / min, and maintain it for 4 hours. When it cools to room temperature, take out the solid powder, and the sample is light yellow. Etch it with 20wt% HF for 12 hours. Finally, wash it with ethanol and water for 2-3 times respectively, place it in a vacuum freeze dryer to freeze-dry the water, and obtain mesoporous C3N4.

[0083] (2) Dissolve 0.4 g of dicyandiamide in 50 mL of deionized water and stir until completely dissolved. Then, add 0.1 g of zinc gluconate to the above solution and stir until completely dissolved. Add 50 mg of ferric acetylacetonate and 0.35 g of the mesoporous g-C3N4 obtained in step (1) to the solution and stir for 1 h. Finally, add 0.6 g of nano-silica beads (30 nm) to the above solution and stir thoroughly at 700 rpm overnight for 18 h. Evaporate the mixed solution to dryness using a rotary evaporator at 55 ° C to obtain a white solid. The dried white solid product is heated to 900 ° C in an Ar atmosphere at a heating rate of 3 ° C / min, and maintained at this temperature for 3 h. After the sample is cooled to room temperature, the obtained product is etched with 20wt% HF for 12 h. Then, by freeze drying, a catalyst without the addition of nano-silica gel dispersion is obtained.

[0084] The TEM image of the Fe-NC nanomaterial prepared in this comparative example is shown in Figure 6 ,from Figure 6 It can be seen that the Fe-NC nanomaterial exhibits a three-dimensional porous material structure, but it can be observed that there is an obvious pore aggregation phenomenon, indicating that the use of nano-silica beads as a template without adding nano-silica gel dispersion will cause a certain aggregation of the pores. From the ORR electrochemical test, the half-wave potential of the catalyst prepared in this comparative example is only 0.781V, which is much lower than the half-wave potential of 0.904V of the catalyst with nano-silica beads (Example 1).

[0085] The comparison results of the catalytic performance of the catalysts of Examples 1-5 and Comparative Examples 1-3 and commercial Pt / C are as follows:

[0086] Table 1: Comparison of half-wave potential, current density and Tafel slope of the catalysts prepared in each example and commercial Pt / C

[0087]

[0088]

[0089] From the comparison results of Examples 1-5 and commercial Pt / C, it can be seen that the half-wave potential of the catalyst of the present invention, especially the catalyst of Example 1, can reach 0.904 V and the current density is 6.89 mA cm -2(0.9V), the Tafel slope is 50mV, both exceeding the performance of commercial Pt / C, and the ORR electrocatalytic performance is better. It can be seen from the comparison results of Example 1 and Comparative Example 1 that the introduction of Fe greatly improves the performance. It can be seen from the comparison results of Example 1 and Comparative Example 2 that the performance of adding only one template of nano-silica gel dispersion is lower than the performance of adding two templates. It can be seen from the comparison results of Example 1 and Comparative Example 3 that the performance of adding only one template of nano-silica spheres is lower than the performance of adding two templates. Therefore, the present invention adopts a dual-template synthesis method, which not only provides sufficient active sites, but also because of its high specific surface area, it can fully disperse Fe single atoms. The Fe-NC nanomaterial synthesized under dual-template conditions contains more mesopores than the conventional single-template synthesized material, which effectively improves the active sites of the Fe-NC nanomaterial and its stability and service life in the oxygen reduction reaction.

[0090] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, the present invention can be implemented in a wide range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principle of the present invention, the application is intended to include any changes, uses or improvements of the present invention, including departing from the disclosed scope in the application and the changes made with conventional techniques known in the art.

Claims

1. A method for preparing Fe-NC nanomaterials, comprising the following steps: (1) evaporating a solution consisting of dicyandiamide, a carbon source, an iron source, mesoporous g-C3N4, nano-silica and water to obtain an evaporation product; The mass ratio of the dicyandiamide, the carbon source, the iron source, the mesoporous g-C3N4, the nano-silicon dioxide and the water is (3-5): 1: (0.5-1): (3-5): (5-7): (400-600); The mesoporous g-C3N4 is prepared according to a method comprising the following steps: 1) Mix cyanamide and nano silica gel dispersion, heat and evaporate to dryness; 2) grinding the solid evaporated from step 1) into powder and calcining; 3) etching the powder after calcination and cooling in step 2) to remove silicon dioxide, and then washing and freeze-drying in sequence to obtain the mesoporous g-C3N4; (2) calcining the evaporated product under an inert atmosphere to obtain a calcined product; (3) After cooling the calcined product, etching is performed to remove silicon dioxide, and after etching is completed, freeze-drying is performed to obtain the Fe-NC nanomaterial.

2. The preparation method according to claim 1, characterized in that: The carbon source is zinc gluconate; The iron source is a divalent iron salt or a trivalent iron salt; The particle size of the nano silicon dioxide is 20-50 nm.

3. The preparation method according to claim 2, characterized in that: The divalent iron salt is ferrous sulfate, ferrous nitrate or ferrous chloride; The trivalent iron salt is ferric acetylacetonate, ferric chloride, ferric nitrate or ferric acetate.

4. The preparation method according to claim 1 or 2, characterized in that: In the step of evaporating a solution consisting of dicyandiamide, a carbon source, an iron source, mesoporous g-C3N4, nano-silicon dioxide and water, the evaporation temperature is 45°C to 65°C.

5. The preparation method according to claim 1 or 2, characterized in that: The conditions for calcining the evaporated product in an inert atmosphere in step (2) are as follows: heating to 700-1000° C. at a heating rate of 2-5° C. / min and maintaining for 2-4 h.

6. The preparation method according to claim 1 or 2, characterized in that: The etching adopts a hydrofluoric acid aqueous solution with a mass concentration of 15% to 30%; The etching time is 6 to 18 h.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the monocyanamide to the nano-silica gel dispersion is (2-3):1; The mass concentration of the nano silica gel dispersion is 20% to 40%; The particle size of the nano silica gel is 20-50 nm.

8. The preparation method according to claim 1, characterized in that: The temperature of heating and evaporating to dryness in step 1) is 110-140°C; The calcination conditions in step 2) are as follows: heating to 400-700°C at a heating rate of 2-5°C / min and maintaining for 3-5h; The etching in step 3) uses a hydrofluoric acid aqueous solution with a mass concentration of 15% to 30%; The etching time in step 3) is 6 to 18 hours.

9. The Fe-NC nanomaterial prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the Fe-NC nanomaterial according to claim 9 in any of the following: A1) Electrocatalytic oxygen reduction reaction; A2) preparing catalysts for electrocatalytic oxygen reduction reaction; A3) Electrocatalytic oxygen reduction reaction in fuel cells; A4) Preparation of fuel cell cathode oxygen reduction reaction catalyst.

Citation Information

Patent Citations

  • Preparation method of mesoporous graphite-phase carbon nitride material

    CN104692344A

  • Preparation and application of nitrogen-iron co-doped biomass porous carbon material

    CN110510596A

  • Iron / ruthenium nitrogen doped porous carbon electrocatalyst as well as preparation method and application thereof

    CN113668012A